Identification and analysis of miRNAs‐lncRNAs‐mRNAs modules involved in stem‐elongation of deepwater rice (Oryza sativa L.). Issue 4 (6th July 2022) - Panda, Alok Kumar; Rawal, Hukam C.; Jain, Priyanka; Mishra, Vishnu; Nishad, Jyoti; Chowrasia, Soni; Sarkar, Ananda K.; Sen, Priyabrata; Naik, Soumendra Kumar; Mondal, Tapan Kumar
Abstract: Deepwater is an abiotic stress that limits rice cultivation worldwide due to recurrent floods. The miRNAs and lncRNAs are two non‐coding RNAs emerging as major regulators of gene expressions under different abiotic stresses. However, the regulation of these two non‐coding RNAs under deepwater stress in rice is still unexplored. In this study, small RNA‐seq and RNA‐seq from internode and node tissues were analyzed to predict deepwater stress responsive miRNAs and lncRNAs, respectively. Additionally, a competitive endogenous RNA (ceRNA) study revealed about 69 and 25 lncRNAs acting as endogenous target mimics (eTM) with the internode and node miRNAs, respectively. In ceRNA analyses, some of the key miRNAs such as miR1850.1, miR1848, and IN‐nov‐miR145 were upregulated while miR159e was downregulated, and their respective eTM lncRNAs and targets were found to have opposite expressions. Moreover, we have transiently expressed one module (IN‐nov‐miR145–Cc‐TCONS_00011544‐Os11g36430.3) in tobacco leaves. The integrated analysis has identified differentially expressed (DE) miRNAs, lncRNAs and their target genes, and the complex regulatory network, which might lead to stem elongation under deepwater stress. In this novel attempt to identify and characterize miRNAs and lncRNAs under deepwater stress in rice, we have provided, probably for the first time, a reference platform to study the interactions of these two non‐coding RNAs with respective target genes through transient expression analyses.